19th century church wall paintings in Russia: the reflection of capital cities’ stylistic trends in the variety of regional murals - Pavlova, Anna L. (Actual Problems of Theory and History of Art, 2012)
In this paper based on the analysis of the Central Russia churches an attempt is made for the first time to reveal the variety of regional stylistic directions and to correlate them with the basic styles of the 19th century painting. The greatest relationship with capital cities’ trends is found in the classicistic wall paintings of the first half of the 19th century; “the late baroque” of the same time is a more independent display of provincial creativity. Th e classicistic tendencies of the eclecticism and the Russian style epoch had a peculiar interpretation on provincial soil. The least influence of capital cities was experienced by the primitivistic direction.
Keywords: Russian art of the 19th century; monumental painting; murals; church art of the Synodal period; regional stylistic trends; baroque; classicism; neo-Russian style